The names of plants - Gledhill, David (Cambridge University Press, 2010)
"The Names of Plants is a handy, two-part reference book for the botanist and amateur gardener. The book begins by documenting the historical problems associated with an ever-increasing number of common names of plants and the resolution of these problems through the introduction of International Codes for both botanic and horticultural nomenclature. It also outlines the rules to be followed when plant breeders name a new species or cultivar of plant." "The second part of the book comprises an alphabetical glossary of generic and specific plant names, and components of these, from which the reader may interpret the existing names of plants and construct new names." "For the third edition, the book has been updated to include explanations of the International Codes for both Botanical Nomenclature (2000) and Nomenclature for Cultivated Plants (1995). The glossary has similarly been expanded to incorporate many more commemorative names."